Indigenous perceptions and adaptive responses to the impacts of climate variability in the Sierra Nevada de Santa Marta, Colombia - Guáqueta-Solórzano, Victoria-Eugenia; Postigo, Julio C. (Frontiers in Climate, 2022)
The exposure, risks, and impacts of climatic changes are most acute for marginalized and disenfranchised groups, particularly Indigenous Peoples. Worldwide, Indigenous Peoples are exposed to a wide range of climate threats that generate a broad spectrum of risks to their wellbeing. Responding to a request from the Arhuaco, this paper examines Arhuaco Indigenous perceptions of climatic variability, the impacts of this variability, and the response to such impacts. The empirical basis of the paper is the fieldwork on four Arhuaco settlements in the Sierra Nevada de Santa Marta, Colombia. We gathered data through surveys, semi-structured interviews, and focus groups. The results of our qualitative and quantitative analyses are: (1) Indigenous perception of climatic variability is consistent with meteorological data; (2) Loss of traditional crops is the most relevant impact; (3) Social and cultural capitals are the most used for adaptation strategies to climate variability; and (4) vulnerability results from non-climatic factors which shape the response capacity to environmental change. Insights from our work contribute to generate new knowledge about impacts of climate variability on Indigenous livelihoods, the responses to such impacts, and to understanding the linkages among climate, capitals, and adaptive responses from marginalized groups in Western society. Finally, our results provide valuable Indigenous practices and perspectives for improving policies to adapt to climate change and strengthen the resilience of local populations.